IoT-Based Chili Plant Watering Automation Using NodeMCU ESP8266 and Blynk when the Pump is Running - Nuril Mustofa; Sunardi Sunardi (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
Automatic plant watering system can help users in caring for plants. Along with the development of technology, it is possible to monitor and control using the Internet of Things (IoT) from anywhere and anytime as long as the device is connected to the internet. The system designed in this study performs watering on chili plant automatically and in real time monitored through the Blynk application on a smartphone. Automation is carried out based on the moisture value parameter obtained from the capacitive soil moisture sensor as input and the NodeMCU ESP8266 as the controller. The output of the system is water sprinkling that comes out through a 12V DC water pump as an actuator and the Blynk application as a monitor and controller via IoT. Automation and monitoring through smartphones using the Blynk application in this study have been successfully carried out. Watering can be done regularly according to predetermined time intervals automatically and the amount of water given to plants according to their needs. At a humidity that is less than 60% and the schedule is appropriate, the pump will run for 4 seconds with a water discharge of 116.32 ml which has been adjusted to the volume of soil and water needs of chili plant.